Identifying the Isoforms of a Novel Muscle-enriched A-type Lamin-Interacting Protein - Shelley, Deeke (Université d'Ottawa / University of Ottawa, 2011)
A novel gene entitled Muscle-enriched A-type Lamin-Interacting Protein, or MLIP was identified through a yeast-two hybrid screen using Lamin A as bait, in an attempt to shed light on the intricate nature of laminopathies. The objective of this study was to identify MLIP’s isoforms. Immunoblotting experiments revealed that MLIP is expressed differentially in both mouse and human tissues. A cloning strategy was performed which demonstrated extensive tissue-dependant alternative splicing, however not all protein bands observed by immunoblotting could be accounted for by the splice variants identified. Hence 5’ and 3’ Rapid Amplification of Complementary DNA Ends was performed, however only a single 5’ and 3’ untranslated region was uncovered. MLIP contains five highly conserved regions of homology, one of which contains a consensus SUMOylation site. MLIP was investigated as a substrate for SUMO through in vitro and in vivo assays, however it was not modified by SUMO. It remains to be determined whether MLIP undergoes other post-translational modification. MLIP’s function has yet to be defined; however preliminary experiments in our laboratory and MLIP’s association with lamin suggest that it may play a role in tissue differentiation.